Impact Of Training Interventions On Dysarthria And Caregivers Stress: A Comparative Study Of Group And Individual Approaches - Dr. Saima Maratab Ali , Dr. Shahnaz Kausar Yousuf , Dr. Sadaf Noveen (Migration Letters, 2024)
Patients with stroke often develop dysarthria, an impairment of speech that has a significant influence on their ability to understand spoken language and overall well-being. Caregiver’ psychological and emotional well-being suffers as a result of the heavy load it imposes on them. Investigation into both individual and group learning therapies is needed to satisfy the requirements of patients as well as caregivers, as there is a lack of evidence on efficient treatment for the condition within people with stroke. This study aims to evaluate how patients with dysarthria respond to both individual and group instructions and to examine the effectiveness of individual and group training for caregivers of patients with dysarthria post stroke in reducing distress as well as improving their quality of life. This study explores the impact of group and individual training interventions on dysarthria patients and stress reduction, as well as quality of life in caregivers of stroke survivors with dysarthria. Applying a randomized controlled trial design, data was collected from n-60 participants across both groups. One that received group training (n-30) and [1]other that received individual training (n-30). Different tools like dysarthria profile, communicative effectiveness index, communicative participation item bank, speech intelligibility test, general health questionnaire, stroke knowledge test and zarit caregiver burden scale were employed to explore the impact of group and individual training interventions on dysarthria patients and stress reduction, as well as quality of life in caregivers of stroke survivors with dysarthria. Statistical Analysis was carried out to assess the correction’s efficacy, comprising the Mann-Whitney U testing. Results indicated that group therapy showed significant improvements in prescribed measuring scales as compared to individual therapy. Overall group therapy yielded better outcomes for both patients and caregivers in managing dysarthria and reducing caregiver stress.